2016
DOI: 10.1175/mwr-d-15-0398.1
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Evaluation of ATHAM-Fluidity, a Nonhydrostatic Atmospheric Model Using Mixed Continuous/Discontinuous Finite Elements and Anisotropic Grid Optimization

Abstract: This paper presents the first attempt to apply the compressible nonhydrostatic Active Tracer High-Resolution Atmospheric Model-Fluidity (ATHAM-Fluidity) solver to a series of idealized atmospheric test cases. ATHAMFluidity uses a hybrid finite-element discretization where pressure is solved on a continuous second-order grid while momentum and scalars are computed on a first-order discontinuous grid (also known as P 1DG 2 P 2 ). ATHAMFluidity operates on two-and three-dimensional unstructured meshes, using tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…The inaccuracies and noise for this problem, as seen for some non-Galerkin treatments, are absent; o2o3 is able to advect a structure along a straight line without generating noise. This result is consistent with that for the first-order Galerkin approach and with that obtained by Savre et al (2016), who reported fewer numerical boundary-related errors for the classic Galerkin method. These results indicate that cut cells may be applicable with polynomial representations higher than one.…”
Section: Fig 10supporting
confidence: 92%
See 1 more Smart Citation
“…The inaccuracies and noise for this problem, as seen for some non-Galerkin treatments, are absent; o2o3 is able to advect a structure along a straight line without generating noise. This result is consistent with that for the first-order Galerkin approach and with that obtained by Savre et al (2016), who reported fewer numerical boundary-related errors for the classic Galerkin method. These results indicate that cut cells may be applicable with polynomial representations higher than one.…”
Section: Fig 10supporting
confidence: 92%
“…Nevertheless, existing atmospheric Galerkin models often do not take advantage of such suitability for good surface approximations, because grids that are not horizontally aligned are typically used. A notable exception is the atmospheric model called Active Tracer High-resolution Atmospheric Model-Fluidity (ATHAM-Fluidity) that uses horizontally aligned cells and achieves good results in the generation of mountain-induced waves (Savre et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Marras 4 / 40 et al (2016) pointed out that element-based Galerkin methods might perform well in next-generation atmospheric and climate models competing with finite difference and spectral transform methods. Savre et al (2016) first introduced the anisotropic adaptive mesh technique into atmospheric modeling in both horizontal and vertical directions and evaluated it with 2D idealized test cases.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we develop a new 3D dynamically adaptive atmospheric model (Fluidity-Atmosphere) based on the dynamic framework of Fluidity, a computational fluid dynamic (CFD) model developed by the Applied Modeling and Computation Group (AMCG), Imperial College London (ICL) (Pain et al 2001(Pain et al , 2005Piggott et al 2009). Its accuracy and conservation properties have been validated by a series of idealized simulations using a uniform mesh, and the computational cost has been decreased by mesh adaptivity in rising bubble, density current and interacting warm and cold bubble tests (Pain et al 2001(Pain et al , 2005Piggott et al 2009;Savre et al 2016;Zheng et al 2015;2020). Fluidity-Atmosphere applies dynamically tetrahedral adaptive meshes in 3D space and time so that regions of steep topography, high dynamic activity or specific interest can be modeled with high horizontal and vertical resolutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation